Sistem Pencarian Lokasi Guru Private Di Kota Pekanbaru Berbasis WEB - Harun Mukhtar; Yulia Fatma; Rizki Yasin (JURNAL FASILKOM, 2021)
Since the pandemic spreads because of Corona Virus in Indonesia, a lot of ways that the government to prevent the spreads. so that the government makes the announcement for school by online and doing teaching and learning at each house. many parents are worried because they feel the teaching and learning activities from home is not enough. therefore is needed to have a system thats able to display information about the location of the private teacher in Pekanbaru.the Geographic system information is a system computer based that combines between the elements of the map and information designed to obtain, process, manipulate, analyze, demonstrate, and display the spacial data to resolve , process and research the problems.this research uses a google maps to showing the information about searching a location and information and data about private teacher